Assessment of green lentil malt as a substrate for gluten-free beer brewing - Alan Gasiński; Joanna Kawa-Rygielska (Scientific Reports, 2024)
Abstract The aim of this study was to analyze whether it is possible to brew beer without using cereals so that the produced beverage could be easily accessible for the population suffering from celiac disease and other gluten-related disorders. Green lentil seeds were malted and then mashed using a congress mashing procedure to assess their advantages and disadvantages in the brewing process. Based on the congress mashing procedure, the mashing process needed to produce beer was developed, and beers were produced from the lentil malts germinated during malting for 96 h, 120 h and 144 h. It was possible to produce beers from the lentil malts; however, they were characterized by a lower alcohol content, lower degree of attenuation and some discrepancies between the concentrations of various volatiles (such as acetaldehyde, ethyl acetate, and 1-propanol) compared to the control beer produced from barley malt.